In vitro antibacterial activity of Croton lechleri on Streptococcus mutans - Avilés Hidalgo, Iván André (2018)
Objective: The purpose of this study was to determine the antibacterial activity of Croton lechleri (C. lechleri) on strains of S. mutans ATCC 35668. Methods: It was used 50%, 75% and 100% concentrations of C. lechleri, and chlorhexidine (0.12%) as a positive control and distilled water as a negative control. It was measured the inhibition halos produced around imbibed discs with each of the concentrations of C. lechleri on colonies of S. mutans which were seeded in Muller Hinton Agar. Results: 75% and 100% of C. lechleri concentration showed antibacterial activity in vitro over S. mutans, 50% concentration showed no activity. 0.12% chlorhexidine concentration showed a higher antibacterial activity in vitro than all the concentrations of C. lechleri groups evaluated. Conclusions: Croton lechleri can be a natural, accessible and low-cost alternative for prevention methods in dental caries when used at 75% and 100%.